PESANTREN DAN TANTANGAN GLOBAL (UPAYA PEMBERDAYAAN PERAN PESANTREN DALAM MENYONGSONG MASA DEPAN BANGSA) - Irfan Musadat; Siti Muawanatul Hasanah (JP : JURNAL PENDIDIKAN, 2019)
Abstract: Changes in living systems are a necessity that does not need to be feared and even resisted, but this is a challenge that makes life dynamic and innovative, then all that remains is how we respond and deal with changes in the living system. Pesantren should not only maintain its existence as an institution of Tafaqquh Fiddin (deepening of religious knowledge, but must explore the role of pesantren in the global era, because that is what today is a necessity of society. So pesantren can act as the transmission of knowledge in Islam, to be the preserver of Islamic religious teachings and to reproduce intellectual printing of the ulama, with the transformation and at the same time cultural acculturation that is happening today which is marked by the development of science and technology science and technology, it will further increase the discourse and treasures for pesantren to improve themselves and introspective in an effort to empower the role of pesantren to meet the future.Keywords: Pesantren, Globalization